FRI0462 UNDERSTANDING MEDIATORS OF PAIN REDUCTION IN PSORIATIC ARTHRITIS PATIENTS TREATED WITH TOFACITINIB: ROLE OF INFLAMMATION. (June 2019) - Taylor, Peter C.; Mease, Philip J.; Bushmakin, Andrew G.; Cappelleri, Joseph C.; Fleischmann, Roy; Fallon, Lara; Woolcott, John; Ogdie, Alexis; Azevedo, Valderilio F.; Vlam, Kurt de
Abstract : Background: Pain is a priority for patients (pts) with psoriatic arthritis (PsA) and physicians. Tofacitinib is an oral Janus kinase inhibitor for the treatment of PsA. As pain is a multidimensional phenomenon, there is growing interest in understanding mechanisms of pain relief during treatment. Objectives: To examine the potential role of inflammation in the effect of tofacitinib on pain in pts with PsA, using mediation modelling. Methods: Data were from the Phase 3 OPAL Broaden (NCT01877668 ) and OPAL Beyond (NCT01882439 ) studies of pts with active PsA treated with tofacitinib 5 mg twice daily (BID) or placebo; pts were tumour necrosis factor inhibitor (TNFi)-naïve or had previous inadequate response (IR) to ≥1 TNFi. All pts continued on a stable dose of a single conventional synthetic DMARD. Analyses used pooled and individual trial data (mean scores from Months 1, 2 and 3). Mediation modelling seeks to explain mechanisms underlying an observed relationship between independent and dependent variables via other explanatory variables (mediators). In this model, pain (100 mm visual analogue scale) was the designated dependent variable, treatment (tofacitinib 5 mg BID vs placebo) the independent variable and inflammation, measured by swollen joint count (SJC) and C-reactive protein (CRP), was a mediator. The primary model designated treatment effect on pain mediated via CRP/SJC as an indirect effect and treatment effect not attributable to CRP/SJC as a direct effect. Models were re-specified based on initial results; model invariance by population (TNFi-naïve vs TNFi-IR pts) was assessed. Results: In the pooled analysis (N=469), 25.9% (p<0.01) of the tofacitinib treatment effect on pain was mediated by CRP/SJC (indirect effect), of which changes via CRP and SJC were 17.8% (p<0.01) and 8.1% (p>0.05), respectively. The treatment effect on pain not attributable to CRP/SJC (direct effect) was 74.1% (p<0.0001). In TNFi-naïve and TNFi-IR pts, indirect effects via SJC were not statistically significant. In the re-specifed model with CRP as sole mediator, the indirect effect was 21.3% for pooled data (p<0.01; Figure A ) and 36.1% (p<0.05) and 16.7% (p<0.05) for TNFi-naïve and TNFi-IR pts, respectively (Figures B, C); the 19.4% difference between TNFi-naïve vs TNFi-IR pts was not statistically significant. Conclusion: While inflammation, as assessed by CRP/SJC, was a significant mediator of the overall treatment effect on pain in tofacitinib-treated pts with PsA, the majority of the treatment effect was not attributable to CRP/SJC changes. When mediators were assessed individually, only CRP was a significant mediator in the pooled analysis. In the re-specified model, CRP-mediated effects differed in TNFi-naïve vs TNFi-IR pts, but this was not statistically significant. These results suggest that CRP/SJC-associated inflammation only partially explains pain in PsA; other potential mediators need to be identified to better understand the treatment effect of tofacitinib on pain. Acknowledgement: Study sponsored by Pfizer Inc. Medical writing support provided by AG McCluskey, PhD, of CMC Connect; funded by Pfizer Inc. Disclosure of Interests: Peter C. Taylor Grant/research support from: Celgene, Galapagos, Eli Lilly, UCB, Consultant for: AbbVie, Galapagos, Gilead, Eli Lilly, Pfizer Inc, Philip J Mease Grant/research support from: AbbVie, Amgen, BMS, Celgene, Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Consultant for: AbbVie, Amgen, BMS, Galapagos, Gilead Sciences, Inc., Janssen, Lilly, Novartis, Pfizer, SUN and UCB, Speakers bureau: AbbVie, Amgen, BMS, Celgene, Genentech, Janssen, Lilly, Novartis, Pfizer and UCB, Andrew G Bushmakin Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Joseph C Cappelleri Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Roy Fleischmann Grant/research support from: AbbVie, Amgen, AstraZeneca, Bristol-Myers Squibb, Celtrion, Genentech, GSK, Janssen, Lilly, Novartis, Pfizer Inc, Sanofi-Aventis, UCB, Consultant for: AbbVie, Amgen, AstraZeneca, Bristol-Myers Squibb, Celtrion, Genentech, GSK, Janssen, Lilly, Novartis, Pfizer Inc, Sanofi-Aventis, UCB, Lara Fallon Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, John Woolcott Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Alexis Ogdie Grant/research support from: (To my university) Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Grant/research support from: Novartis, Pfizer, Consultant for: AbbVie, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly and Company, Novartis, Pfizer, and Takeda, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Corrona, Eli Lilly, Novartis, Pfizer Inc, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Consultant for: Abbvie, Amgen, BMS, Celgene, Corrona, Lilly, Novartis, Pfizer, Takeda, Valderilio F Azevedo Grant/research support from: AbbVie, GSK, Janssen, Merck Serono, Novartis, Pfizer Inc, UCB, Consultant for: AbbVie, GSK, Janssen, Merck Serono, Novartis, Pfizer Inc, UCB, Kurt de Vlam Consultant for: Pfizer Inc, Consultant for: Johnson & Johnson